Fluoride concentration in bottled water: a systematic review - Ceci Queluz Venturini; Paulo Frazão (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2015)
Abstract This study aimed to summarize major methodological features and main findings described in the studies on fluoride concentration monitoring in bottled water, published in specialized journals between 2008 and 2012, highlighting their implications for public health surveillance. A systematic review was conducted searching scientific articles in the databases: Lilacs, PubMed and Scopus. Twenty-two articles from the world's main continents were included: 68.2% informed both the number of samples and brands collected; 81.8% examined products collected in only a city or metropolitan area; 77.3% assessed the outcomes using a sound criterion; 45.5% compared the values of fluoride measured in the sample and those informed in the label, being noted significant discrepancies. In conclusion, the discrepancy between the found amount and the informed concentration in the label was quite common reinforcing the warnings raised by several researchers. The parameters that define hazard to health and instruct the content of labelling should be revised. There is an important room for improvement of the methodological procedures in further studies.